Species delimitation in Amana (Liliaceae): transcriptomes battle with evolutionary complexity - Wang, Mei‐Zhen; Wu, Jing; Zhang, Sheng‐Lu; Mao, Li‐Mi; Ohi‐Toma, Tetsuo; Takano, Atsuko; Zhang, Yong‐Hua; Cameron, Kenneth M.; Li, Pan (Cladistics, 2024)
Species delimitation has long been a subject of controversy, and there are many alternative concepts and approaches used to define species in plants. The genus Amana (Liliaceae), known as ”East Asian tulips” has a number of cryptic species and a huge genome size (1C = 21.48–57.35 pg). It also is intriguing how such a spring ephemeral genus thrives in subtropical areas. However, phylogenetic relationships and species delimitation within Amana are challenging. Here we included all species and 84 populations of Amana , which are collected throughout its distribution range. A variety of methods were used to clarify its species relationships based on a combination of morphological, ecological, genetic, evolutionary and phylogenetic species concepts. This evidence supports the recognition of at least 12 species in Amana . Moreover, we explored the complex evolutionary history within the genus and detected several historical hybridization and introgression events based on phylogenetic trees (transcriptomic and plastid), phylonetworks, admixture and ABBA‐BABA analyses. Morphological traits have undergone parallel evolution in the genus. This spring ephemeral genus might have originated from a temperate region, yet finally thrives in subtropical areas, and three hypotheses about its adaptive evolution are proposed for future testing. In addition, we propose a new species, Amana polymorpha , from eastern Zhejiang Province, China. This research also demonstrates that molecular evidence at the genome level (such as transcriptomes) has greatly improved the accuracy and reasonability of species delimitation and taxon classification.